2018
DOI: 10.1128/jb.00086-18
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of PASTA Kinase and Two-Component Signaling in Response to Cell Wall Stress in Enterococcus faecalis

Abstract: Two common signal transduction mechanisms used by bacteria to sense and respond to changing environments are two-component systems (TCSs) and eukaryotic-like Ser/Thr kinases and phosphatases (eSTK/Ps). is a Gram-positive bacterium and serious opportunistic pathogen that relies on both a TCS and an eSTK/P pathway for intrinsic resistance to cell wall-targeting antibiotics. The TCS consists of a histidine kinase (CroS) and response regulator (CroR) that become activated upon exposure of cells to cell wall-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…For example, we observed mutations in genes for drug targets associated with protein synthesis inhibitors ( rpsJ [66], 30S ribosomal protein S5 [ rpsE ] [67]) and fluoroquinolones (DNA topoisomerase 4 subunit A [ parC ]; DNA gyrase subunit A, [ gyrA ] [68]). We also identified mutations in a sensor histidine kinase [69, 70] ( EF3290 ) in populations selected by cell wall inhibitors and mutations in 23S rRNA genes in the LZD-selected population [64, 71]. Surprisingly, the DAP-selected population did not contain mutations in genes previously identified with DAP resistance [57, 58], though we observe a mutation in rpsJ in both the clonal and population sequences.…”
Section: Resultsmentioning
confidence: 84%
“…For example, we observed mutations in genes for drug targets associated with protein synthesis inhibitors ( rpsJ [66], 30S ribosomal protein S5 [ rpsE ] [67]) and fluoroquinolones (DNA topoisomerase 4 subunit A [ parC ]; DNA gyrase subunit A, [ gyrA ] [68]). We also identified mutations in a sensor histidine kinase [69, 70] ( EF3290 ) in populations selected by cell wall inhibitors and mutations in 23S rRNA genes in the LZD-selected population [64, 71]. Surprisingly, the DAP-selected population did not contain mutations in genes previously identified with DAP resistance [57, 58], though we observe a mutation in rpsJ in both the clonal and population sequences.…”
Section: Resultsmentioning
confidence: 84%
“…The ireK encoded transmembrane Ser/Thr kinase regulates cell wall homeostasis, antimicrobial resistance, and contributes to bacterial fitness during long-term colonization of the intestinal tract [61, 67, 68]. Recently it has been shown that direct cross-talk between IreK and the CroS/R system positively impacts enterococcal cephalosporin resistance [69].…”
Section: Resultsmentioning
confidence: 99%
“…Here, we show that all three epa mutants exhibit significantly increased resistance to ceftriaxone, a type of cephalosporin. It has been previously reported that intrinsic cephalosporin resistance is mediated by a eukaryotic-like Ser/Thr kinase, IreK, formerly known as PrkC (29), and by the CroRS two-component regulatory system (30), and that these two signaling systems are intertwined (31). IreK is thought to monitor cell wall integrity and respond to cell wall stress (29).…”
Section: Discussionmentioning
confidence: 99%